Mesopotamian gods & goddesses - Hale, Vincent; Garvey, Brian (New York : Britannica Educational Publishing : Rosen Publishing, 2014)
This volume provides a glimpse of the cradle of civilization by examining Mesopotamian religious and mythological beliefs as well as some of the gods and goddesses at the core of their stories. It also looks at epics--such as that of Gilgamesh--and other aspects of Mesopotamian life.
Chapter 1. The history and literature of Mesopotamia -- chapter 2. The Mesopotamian worldview as expressed in myth -- chapter 3. Gods and goddesses.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Mythology, Assyro-Babylonian.; Gods, Assyro-Babylonian.; Goddesses, Assyro-Babylonian.; Civilization, Assyro-Babylonian.; BODY, MIND & SPIRIT / Spirituality / Paganism & Neo-Paganism; RELIGION / Comparative Religion; Electronic books